The effect of the disability fund on individual livelihoods: a case study of persons with disabilities in the Atwima Nwabiagya District of the Ashanti Region of Ghana - Agyemang, Esther Fredua (2016)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master of Science Disability Rehabilitation and Development.